Neural Basis and Motor Imagery Intervention Methodology Based on Neuroimaging Studies in Children With Developmental Coordination Disorders: A Review - Irie, Keisuke; Matsumoto, Amiri; Zhao, Shuo; Kato, Toshihiro; Liang, Nan (Frontiers in Human Neuroscience, 2021)
Although the neural bases of the brain associated with movement disorders in children with developmental coordination disorder (DCD) are becoming clearer, the information is not sufficient because of the lack of extensive brain function research. Therefore, it is controversial about effective intervention methods focusing on brain function. One of the rehabilitation techniques for movement disorders involves intervention using motor imagery (MI). MI is often used for movement disorders, but most studies involve adults and healthy children, and the MI method for children with DCD has not been studied in detail. Therefore, we conducted a review to update the information on the associated neural bases and to clarify the methodology of interventions using MI for children with DCD. The neuroimaging review included 19 magnetic resonance imaging studies, and the neurorehabilitation review included four MI intervention studies. In addition to previously reported neural bases, our results indicate decreased activity of the bilateral thalamus, decreased connectivity of the sensory motor cortex and the left posterior middle temporal gyrus, bilateral posterior cingulate cortex (Brodmann area [BA]23, 31), precuneus (BA7, 31), cerebellum, and basal ganglia, loss of connectivity superiority in the abovementioned areas, and reduction of gray matter volume in the right superior frontal gyrus (BA6) and middle frontal gyrus (BA6, 8). Regarding of characteristic of the MI methods was that participants observed a video related to motor skills before the intervention. In addition, they performed visual motor tasks prior to MI training sessions, and MI was performed before, during, and after physical practice. The MI focused on motor tasks that the performance was poor in children with DCD. The intervention was carried out for 60 minutes per week for a total of 5 weeks (300 minutes in total) in two studies, and for 45 minutes per week for 9 weeks in one study (405 minutes in total). Our results indicate that, for children with DCD, performing visual motor tasks prior to MI intervention and performing MI with action observation could ameliorate the deactivation of the neural base.